Pengaruh Perubahan Vakum dan Temperatur Pemanas Fresh Water Generator terhadap Produksi Air Tawar di MT. PM REGENT - Heri Kiswanto; Susanto Susanto; Khaeroman; Yulius Oscar; Ngatmin Ngatmin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2024)
Fresh onboard water is required to fulfill the crew's living needs and support the ship's operations. The need for fresh water for the crew and operational support of the boat is fulfilled with fresh water purchased from the land. Water purchases can be made when the ship is in port, either when the ship is at the dock or when the boat is anchored. Additional fresh water supply can be obtained continuously while the ship is sailing. Seawater desalination is a solution to produce fresh water to fulfill the new water needs. Desalination using a freshwater generator (FWG) involves evaporation and condensation processes affected by vacuum and operating temperature. This study was conducted to determine the effect of changes in pressure and temperature parameters on the production capacity of the freshwater generator. The study was conducted using a case study method through observation, and experimentation on board MT.PM REGENT. The vacuum in the FWG chamber was varied based on the suction of the vacuum ejector. Hot water temperature as a heater in the evaporator is taken from the cooling jacket of the main engine. The result of the pump ejector pressure variation greatly affects the vacuum level of the distillation chamber At pump ejector pressures between 8 – 16 Bar, the vacuum rate can reach 99 – 100% after the pump is operated At pressures of 2 and 4 Bar, the vacuum level drops dramatically, reaching only 50 and 80 %, respectively. The lowest production of FWG when operated with 80% vacuum with a heating temperature of 75 OC is 2767 liters/day. In FWG operation with a maximum vacuum of 100% and a heating temperature of 85 OC, it is able to produce the most fresh water around 6879 liters/day. Based on the changes in parameters, it can be concluded that a decrease in the level of vacuum and heater temperature reduces the production of fresh water from the Fresh Water Generator.